The Social Construction of Chinese Models of Teaching - Daniel D. Pratt; Mavis Kelly; Winnie Wong (Adult Education Research Conference, 1998)
Five principal relationships, derived from long-standing Confucian values, are described as the cultural and social foundation for Chinese models of teaching. Three related models of teaching will be described during the presentation: Teacher as master; teacher as virtuoso; and teacher as coach.